Science and the Dragon: Redistributing the Treasure of Knowledge - Bardi, Ugo; Perissi, Ilaria; Chiavenuto, Luisella; Lavacchi, Alessandro (Organisms. Journal of Biological Sciences, 2022)
We start from an analogy: science can be seen as one of the dragons of Western mythology, described as sitting on their hoard of gold but not using it for any useful purpose. Similarly, scientists seem to be content with accumulating knowledge, doing little or nothing to use it outside their restricted domain of expertise. We argue that this attitude is one of the elements causing the ongoing decline of science as a way to produce innovative knowledge. We propose that the situation could be improved by encouraging scientific communication and the redistribution of the scientific treasure of knowledge in the form of “mind-sized” memes.